Transcatheter closure of ruptured sinus of Valsalva: Different techniques and mid‐term follow‐up. Issue 3 (10th August 2015) - Mahimarangaiah, Jayranganath; Chandra, Subash; Subramanian, Anand; Srinivasa, K. H.; Usha, M. K.; Manjunath, C. N.
Abstract : Objectives: The aim of the present study was to study the feasibility and approaches to device closure of ruptured sinus of Valsalva (RSOV). We have compared the advantages and disadvantages of different devices and techniques and discussed complications which might occur during or after the procedure. Background: There are only a few case series of transcatheter closure of RSOV, with most cases being traditionally referred for surgery. We have employed different devices used for treatment of congenital shunt lesions to achieve closure. Reasons for failure and need for surgical referral have also been analyzed. Methods: Transcatheter closure was attempted in a total of 25 patients of RSOV who presented to us over a period of 4 years. Different devices were deployed using antegrade and retrograde approaches. All patients have been on regular follow‐up. Results: The procedural success rate was 84%. Two patients presenting in cardiogenic shock were effectively treated by device closure. There was one case of device embolization and two patients had residual leak. Three patients were referred for surgery. There was one case of device induced severe aortic regurgitation. Ventricular septal defect and RSOV were closed simultaneously in one patient. Conclusions: Different approaches and devices may be used for transcatheter closure of RSOV. We prefer antegrade closure using duct occluders in most cases while muscular VSD occluders may be used in select situations. ADO II devices should hardly ever be used on their own for device closure of RSOV. © 2015 Wiley Periodicals, Inc.